Non-Saponifiable Components of Xanthium strumarium Leaves (Linn.) - Saxena, V.K.; Mishra, Maju (Asian Journal of Chemistry, 2010)
The present paper deals with the isolation of a number of compounds from petrol fractions which were identified as β-sitosterol, β-amyrin, stigmasterol and n-octacosanol by spectral and chemical analysis.